Local Fruit Sdn Bhd - Jailis, Blasius; Meyrick, Erikly Effyfian; Edmond, Evindrick; Samad, Hairul Azman; Karis, Raziman (2014)
The name of our company is LOCAL FRUIT SDN BHD; this company provides product and service in the operation process to gain profitability. The product that we supply is local fruits from our farm or from the farmer that sender their fruit to our factory such as bambangan, rambutan, durian, banana pineapple, coconut, Jack fruit, Citrus and mango. Other than that, our company also supply original juice from the local's fruits it is. For the service, we supply the good natural environment especially to the visitors that come in our factory because we also stand for agro tourism that encourage local people and outside visitors to come in our company to looking the amazing building that we created from the shape of locals fruits. We also provide the package especially to the student that want to complete their study of research related with the plant such as plants pest and disease, soil science and etc. The main office including the location of this organization at Sugut Beluran. We choose this places because easy for us to get resources a long of years. Other hand its strategic location especially to the agro tourism because most of the jungle at there is natural beauty so that the visitors can enjoy along of their journey to the farm. We are prospecting to increase 3 % and 5 % sales of our business on second and third year respectively.